Asociación entre obesidad y depresión infantil, en pacientes de 7 a 17 años de edad, atendidos en consultorios externos del Hospital III EsSalud - Iquitos, período 2024 - Michuy Zegarra, Oshiro Javier (2024)
INTRODUCTION: Childhood obesity is a public health problem in many developing countries. In the case of our country, in the department of Loreto, there are cases of obesity and overweight in the child population, and it could represent a risk factor for depression in this age group, which is why the purpose of the present study is to identify its association between obese vs. non-obese patients in relation to childhood depression. OBJECTIVE: To determine if there is an association between obesity and childhood depression, in patients between 7 and 17 years of age, treated in outpatient clinics of the Hospital III EsSalud - Iquitos, period 2024. METHODOLOGY: The present study is observational, analytical (cases and controls), cross-sectional, prospective. With the final sample with which we work, two groups of patients will be compared, the first group with the condition under study (obese) that would represent the cases, and a second group that does not have the condition, that is, the non-obese, that would represent the controls. For this purpose, the confidence level that will be set is 95%, and an error of 5% will be assumed. With the formula applied, the sample size is 291 patients, with random selection. The statistical analysis of the survey will be carried out with the statistical program SPSS version 25.0 and Excel. The results will be shown with graphs in univariate and bivariate frequency tables. The association hypothesis will be demonstrated. RESULTS: Once approval of the academic work has been obtained, evaluation and permission will be requested from the Research Committee and Ethics Committee of Hospital III EsSalud Iquitos; The collection of information will be taken from the surveys that will be carried out on pediatric patients who attend the outpatient clinics of Hospital III EsSalud Iquitos, and who meet the inclusion criteria. CONCLUSION: The conclusions will be obtained according to the results.